2017
DOI: 10.4103/jispcd.jispcd_414_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and perceived confidence in the management of medical emergencies in the dental office: A survey among the dental students and interns

Abstract: Aims and Objectives:Many situations in the dental office can provoke medical emergencies. Lack of training and inability to overcome the medical emergencies can lead to serious consequences and legal actions. The aim of the study is to investigate and assess the knowledge, attitude, and perceived confidence of dental students and interns in the management of medical emergency.Materials and Methods:A self-administered structured questionnaire was distributed to 153 of the undergraduate dental students and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…In the present study, the majority of the population 97% obtained the vital signs, 3% population did not obtain the vital signs Figure 8. This result is similar to the study done by Haifa Fahad Albelaihi et al Among 50 participants 29.4% of the participants mentioned obtaining vital signs before commencing any treatment, while 20.3% of them did not (Alshahrani et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…In the present study, the majority of the population 97% obtained the vital signs, 3% population did not obtain the vital signs Figure 8. This result is similar to the study done by Haifa Fahad Albelaihi et al Among 50 participants 29.4% of the participants mentioned obtaining vital signs before commencing any treatment, while 20.3% of them did not (Alshahrani et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, as the amount of emergency materials stored changes, the material storage warehouse may also need to adjust its structure or expand its scale. At this time, the technology can help managers find the materials that need to be transferred and ensure the orderly progress of the entire transfer [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Syncope was one of the most common medical emergencies in the current study, which was consistent to the studies from multiple countries. [2,7,10] It is suggested that dentists should pay more attention to prevention, early diagnosis of these common but less fatal adverse events, and be prepared with pain and anxiety relief methods for effective management. [5,[11][12][13][14] In the current study, hypoglycemia (30.3%) and…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Studies showed that there was an alarming lack of preparation for dentists to respond to medical emergencies in the dental clinics. [1,7,8] Although many medical institutions in China provide This study aimed to analyze the feature, frequency, and associated factors for dentists experiencing medical emergencies in China, and provide evidence for dental institutions developing training for dentists on the targeted medical emergency response.…”
mentioning
confidence: 99%